2009
DOI: 10.1134/s0006297909110054
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobin and mitochondria: Oxymyoglobin interacts with mitochondrial membrane during deoxygenation

Abstract: The rates of oxygen uptake by rat liver mitochondria (MC) (native coupled, freshly frozen, and uncoupled by FCCP) have been measured polarographically in the absence (V(0)) or presence (V(1)) of 0.11-0.25 mM sperm whale MbO2. Under the same standard conditions, the rate of sperm whale MbO2 deoxygenation (V(2)) has been studied spectrophotometrically in the presence of respiring MC. For freshly frozen MC, the dependence of V(1) and V(2) on the overall charge of MbO2 has been investigated at pH 5.6-7.6, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
1
25
1
Order By: Relevance
“…through site-directed mutagenesis). Interestingly, recent studies indicate that oxy-Mb interacts with mitochondria in the muscle cells, initiating a conformational change in the oxy-Mb during the release of oxygen (40,41). These results must be taken into account in future studies of the retention of fatty acids or acylcarnitines when bound to oxy-Mb that may simultaneously release both oxygen and lipids to the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…through site-directed mutagenesis). Interestingly, recent studies indicate that oxy-Mb interacts with mitochondria in the muscle cells, initiating a conformational change in the oxy-Mb during the release of oxygen (40,41). These results must be taken into account in future studies of the retention of fatty acids or acylcarnitines when bound to oxy-Mb that may simultaneously release both oxygen and lipids to the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Because previous studies have shown mitochondrial localization of Mb (Postnikova et al 2009) and interaction with COX IV, a subunit comprising respiratory complex IV (Yamada et al 2013), a new hypothesis proposing interaction between mitochondrial protein and Mb (Mito-Mb) has emerged, which identifies the underlying mechanisms for a direct role for Mb in interacting with complex IV to modulate mitochondrial respiration. Therefore, we hypothesized that the direct Mb interaction in the mitochondria (mito-Mb) improves complex IV activity.…”
Section: Introductionmentioning
confidence: 99%
“…We first showed that O 2 release from MbO 2 at physiological p O2 values proceeds only upon direct contact of the protein with mitochondria [16,17]. If respiring mitochondria are separated from MbO 2 solution by a semipermeable membrane (mitochondria are inside a closed dialysis bag), no MbO 2 deoxygenation occurs even at near-zero O 2 concentration ( Figure 1a).…”
Section: Oxymyoglobin Interacts With Mitochondrial Membrane During Dementioning
confidence: 99%
“…The rate of oxygen release from MbO 2 in the presence of mitochondria (V 2 ) measured spectrophotometrically ( Figure 1b) is constant during the entire period of the oxy-deoxy transition (τ tr ) and does not depend on MbO 2 concentration (the 0-th order in myoglobin). Indeed, no reaction rate changes are observed with increasing MbO 2 concentration more than twofold (Table 1) [16,17]. Lowering the reaction order in comparison with 1st-order reaction of MbO 2 deoxygenation in solution (Equation 1) is inherent for different processes with participation of membranes [18].…”
Section: Oxymyoglobin Interacts With Mitochondrial Membrane During Dementioning
confidence: 99%
See 1 more Smart Citation